Airborne or Droplet Precautions for Health Workers Treating Coronavirus Disease 2019?. (4th May 2022) - Bahl, Prateek; Doolan, Con; de Silva, Charitha; Chughtai, Abrar Ahmad; Bourouiba, Lydia; MacIntyre, C Raina
Abstract: Cases of coronavirus disease 2019 (COVID-19) have been reported in more than 200 countries. Thousands of health workers have been infected, and outbreaks have occurred in hospitals, aged care facilities, and prisons. The World Health Organization (WHO) has issued guidelines for contact and droplet precautions for healthcare workers caring for suspected COVID-19 patients, whereas the US Centers for Disease Control and Prevention (CDC) has initially recommended airborne precautions. The 1- to 2-meter (≈3–6 feet) rule of spatial separation is central to droplet precautions and assumes that large droplets do not travel further than 2 meters (≈6 feet). We aimed to review the evidence for horizontal distance traveled by droplets and the guidelines issued by the WHO, CDC, and European Centre for Disease Prevention and Control on respiratory protection for COVID-19. We found that the evidence base for current guidelines is sparse, and the available data do not support the 1- to 2-meter (≈3–6 feet) rule of spatial separation. Of 10 studies on horizontal droplet distance, 8 showed droplets travel more than 2 meters (≈6 feet), in some cases up to 8 meters (≈26 feet). Several studies of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) support aerosol transmission, and 1 study documented virus at a distance of 4 meters (≈13 feet) from the patient. Moreover, evidence suggests that infections cannot neatly be separated into the dichotomy of droplet versus airborne transmission routes. Available studies also show that SARS-CoV-2 can be detected in the air, and remain viable 3 hours after aerosolization. The weight of combined evidence supports airborne precautions for the occupational health and safety of health workers treating patients with COVID-19. Abstract : At present, the limited available evidence does not support droplet precautions and 1- to 2-meter (≈3–6 feet) rule of special separation being adequate for occupational health and safety of health workers treating patients with COVID-19.